Project-based learning and its implementation in primary school music classes - Monreal Guerrero, Inés María; Berrón Ruiz, Elena (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2019)
Project-based learning, as an active methodology, has made its incursion into schools mainly after the implementation of the Organic Law 8/2013, of 9 December, for the improvement of the quality of education –LOMCE–. The methodological application of the PBL necessarily requires specific permanent training and adjusted to each teacher group. The research we present focuses on the music education specialist teaching collective that teaches in the primary stage of the province of Avila. We have tried to know the specific training referred to in PBL and its application in the music classroom. The study has used a preferably qualitative methodology and the conclusions determine the lack of training in PBL for teachers linked to the lack of implementation of this methodology, despite which they consider it innovative, inclusive, sustainable and transferable.
Keywords: Project based learning; Active methodologies; Primary education; Music education; Active learning.; Active learning